1994
DOI: 10.1002/cbm.1994.4.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Current provision and recommendations for the management of psychosocial morbidity following disaster in England

Abstract: Although disasters remain statistically rare events, the last decade has seen an increase in the number of major incidents affecting the UK. Concurrent with this increase has come clinical data, showing how psychosocial health may be adversely affected by disasters. There is good evidence that many victims of traumat~ ic stress suffer from depression and suicidal behaviour; two of the English Department of Health's stated objectives for reduction in their publication, Health of the Nation. The objectives of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In 1989, the Department of Health funded a study by the Allen Disaster Working Party, and its published report (Allen, 1991) provided helpful advice regarding the provision of protocols for psychosocial support, the distribution of information and liaison with the media. However, a subsequent follow-up study conducted by Adshead et al (1993) revealed that very few local authorities had made any effort to implement the Allen recommendations. This is perhaps not surprising since the history of trauma confirms a striking and consistent tendency among communities to deny the reality of suffering (e.g.…”
Section: What Are Appropriate Methods Of Early Mental Health Intervenmentioning
confidence: 99%
“…In 1989, the Department of Health funded a study by the Allen Disaster Working Party, and its published report (Allen, 1991) provided helpful advice regarding the provision of protocols for psychosocial support, the distribution of information and liaison with the media. However, a subsequent follow-up study conducted by Adshead et al (1993) revealed that very few local authorities had made any effort to implement the Allen recommendations. This is perhaps not surprising since the history of trauma confirms a striking and consistent tendency among communities to deny the reality of suffering (e.g.…”
Section: What Are Appropriate Methods Of Early Mental Health Intervenmentioning
confidence: 99%
“…North American communities developed strategies for disaster response (National Institute for Mental Health (NIMH), 1978, 1986 and Adshead et al (1994) described a three-part model for post-trauma response for UK local authorities in the event of major disasters which included a post-trauma debriefing process. Rick et al (1998) found debriefing to be the most commonly used form of post-trauma intervention in UK organisations.…”
Section: The Use Of Psychological Debriefingmentioning
confidence: 99%
“…Following recommendations to the Department of Health in 1991 (Allen, 1991), major disaster response plans made by local authorities now increasingly include a psychosocial component. However, Adshead et al (1993) found a very mixed picture when reviewing planned service provision in the wake of a disaster. If plans do not address the psychological needs of disaster victims and their relatives it means that large numbers of people, while receiving appropriate physical care, may not receive appropriate psychological care.…”
Section: Major Disastermentioning
confidence: 99%